2020
DOI: 10.21203/rs.3.rs-95370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study the Effect of Temperature on Methane Desorption Based on Thermodynamics and Kinetics

Abstract: Desorption hysteresis is important for primary gas production. Temperature may cause serious change in the methane adsorption/desorption behaviors. In order to study the mechanism of methane desorption and desorption hysteresis, three sets of samples of long flame coal, coking coal, and anthracite were collected, and experiments such as microscopic composition determination, liquid nitrogen adsorption, and isothermal adsorption/desorption were performed. From the perspectives of desorption kinetics, desorption… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Many scholars believed that there is a critical temperature point (CTP) that makes the maximum adsorption capacity or the adsorption amount at a certain gas pressure show a trend of a rapid decrease at first and then basically unchanged. 8,19 It should be noted that the maximum test temperatures are 70 and 100 °C in the studies of Guan et al 8 and Zheng et al, 19 respectively, which are significantly greater than the maximum temperatures in the studies of this paper and Gao et al 60 The two different results may have a lot to do with the maximum test temperature. The amount of gas adsorbed by coal is related to the two kinds of molecular interactions: the solid/gas interaction and the gas/gas interaction.…”
Section: Influence Of Temperature On Adsorption Parametersmentioning
confidence: 57%
See 1 more Smart Citation
“…Many scholars believed that there is a critical temperature point (CTP) that makes the maximum adsorption capacity or the adsorption amount at a certain gas pressure show a trend of a rapid decrease at first and then basically unchanged. 8,19 It should be noted that the maximum test temperatures are 70 and 100 °C in the studies of Guan et al 8 and Zheng et al, 19 respectively, which are significantly greater than the maximum temperatures in the studies of this paper and Gao et al 60 The two different results may have a lot to do with the maximum test temperature. The amount of gas adsorbed by coal is related to the two kinds of molecular interactions: the solid/gas interaction and the gas/gas interaction.…”
Section: Influence Of Temperature On Adsorption Parametersmentioning
confidence: 57%
“…Similarly, Gao et al 60 also found that the saturated methane adsorption capacity of coal has a linear negative correlation with the temperature range of 25−45 °C. However, the weakening extent of temperature increase on the gas adsorption capacity of coal is not invariable.…”
Section: Influence Of Temperature On Adsorption Parametersmentioning
confidence: 75%
“…When the pressure increases to a certain extent, the increase rate of adsorption amount gradually slows down. The adsorption capacity of coal to methane decreases with the increase of temperature under the same pressure(Chen et al, 2021; Gao et al, 2021; Zheng et al, 2021). Comparing the relationship between DFS and GJH temperature and adsorption capacity, it is found that the adsorption capacity increased by 4–4.7m 3 /t, when the pressure increased from 1 MPa to 4 MPa (Figure 16).…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Through analysis of the change laws of the Langmuir effective diffusion coefficient with the coal rank and their influencing factors, Yan 26 found that a rise in the coal rank increased the development degree of micropores and gas desorption capacity. Wang, 27 Gao, 28 and Lin 29 concluded a higher adsorption pressure of coal mass is related to the stronger movement of methane molecules, more favorable for gas desorption, and accelerates gas diffusion. Additionally, the high pressure increases the diffusion coefficient and the cumulative amount of gas desorption and diffusion.…”
Section: ■ Introductionmentioning
confidence: 99%